Broadcasting in the triangle: negotiating colonial identity and race in Bermuda's emerging media industries - Selassie, Dana (2017)
Caught within a triangle of identity, Bermuda posits itself today as colonized-British, but not English; Americanized, but not American; having deeply rooted ties to the Afro-Caribbean, yet, not a part of the West Indies, situating itself as an exemplar of cultural hybridity. With its political ties with Britain as the oldest colony in the British Empire, questions of identity become even more complex for Bermuda when historical narratives such as slavery, war and contestations of colonial power and control are woven into the social, economic and cultural fabric of the island. Likewise, the complicated and ambiguous relationship between national identity and broadcasting presents further challenge to Bermuda as its hybrid colonial broadcasting system intricately ties into its transitioning, and at times, tempestuous colonial identity.